Pengembangan Moderasi Beragama di Era Teknologi Informasi dan Komunikasi 4.0 - Pardianto, Pardianto; A’la, Abd (Jurnal Ilmu Komunikasi, 2023)
It is common knowledge that the information and communication technology revolution 4.0 has resulted in great impacts on the dynamics of social life, including the religious moderatism development. This research discusses the challenges and opportunities in developing religious moderation in the era of information and communication technology 4.0. Using a library research method, the findings illustrate; first, the era of information and communication technology 4.0 affords a change to provide insight into technological innovation that can be used to design platforms to support religious dialogue. Second, Information and Communication Technology 4.0 is utilized as a strategy and innovation in promoting dialogue and harmonious understanding between religious communities. Third, the challenge faced is new technology development is likely to open the door of different religious understanding that can become a source of conflict and polarization. Hence, overcoming the challenges requires education and digital literacy as the main foundation in empowering the community in dealing with fluctuations in religious information.